Generalized de Jonqui`eres divisors on generic curves - FARKAS, Gavril (Studia Universitatis Babeș-Bolyai Mathematica, 2023)
The classical de Jonqui`eres and MacDonald formulas describe the virtual number of divisors with prescribed multiplicities in a linear system on an algebraic curve. We discuss the enumerative validity of the de Jonqui`eres formulas for a general curve of genus g. Mathematics Subject Classification (2010): 14H10, 14H51. Received 14 October 2022; Revised 05 February 2023. Published Online: 2023-03-20. Published Print: 2023-04-30